"Belonging is a luxury to us": International graduate students’ sense of belonging at a predominantly White institution in the U.S. - Paik, Eun Jung; Braxton, Marcelius (Journal of International Students, 2026)
This qualitative study explores international graduate students’ sense of belonging at a predominantly white institution (PWI) in the northeastern United States. Drawing on focus group interviews with 12 students from diverse academic disciplines, this study examines how institutional, academic, and sociocultural contexts shape their experiences of belonging. The analysis identified six key themes: (1) fragmented social belonging; (2) heavy reliance on ethnic communities; (3) academic belonging contingent on funding, advisor support, and research alignment; (4) language proficiency and pressure to prove oneself constantly; (5) performative versus genuine diversity, equity, and inclusion (DEI) efforts; and (6) the importance of physical and symbolic space. While participants appreciated some aspects of academic support, many reported marginalization related to language-based bias, limited cultural understanding, and underrepresentation. The study highlights the importance of intentional, equity-driven institutional practices and concludes with six actionable recommendations to enhance the academic and social integration of international graduate students.